MABC-2 pro děti s poruchou autistického spektra Manuál pro metodiku šetření dětí testem motoriky MABC-2 - Možná, Tereza (Masaryk University Press, 2022)
Title in English: MABC-2 for children with autism spectrum disorder. Manual for the MABC-2 motor skills test for children Autism spectrum disorders (ASD) are neuro-developmental pervasive multifactorial diseases of unknown aetiology that are often associated with a significant impairment of motor skills and a delay in motor development. With the rapidly increasing prevalence of these disorders in the Czech Republic and worldwide, the possibilities of diagnosing the motor skills of children with ASD are an increasingly important priority. The research modified the standard administration and implementation process of the Movement Assessment Battery for Children, 2nd edition (MABC-2) by designing modifications that utilize fundamental principles of structured learning and the TEACCH program. In particular, these elements: Individualization, Structuralization, Visualization and Motivation, were implicated in the entire process of testing children's motor skills with the MABC-2 Test.